Performance Analysis and Comparison of Full Chip and Half Chip Rate DC and NC Code Acquisition in MIMO DSCDMA over Uncorrelated Rayleigh Wireless Channel. (16th May 2011) - Kumar, N. Sathish; Shankar Kumar, K. R.
Abstract : This paper presents the performance analysis and comparison of full chip and half chip rate of noncoherent (NC) and differentially coherent (DC) code acquisition scheme in (multiple input-multiple output) MIMO assisted by direct sequence spread spectrum (DS-CDMA) wireless system when communicated over uncorrelated Rayleigh channel. Four schemes are investigated, namely, SISO with full chip rate, SISO with Half chip rate, MIMO with full chip rate, and MIMO with half chip rate by varying the code acquisition technique. The simulation is done in RF signal processing Lab using matlab tool box, and the performance metrics are considered, namely, Bit Error Rate (BER) and mean acquisition time (MAT). The simulation results indicate that DC performance is superior than NC in both full chip and half chip rate and also shown that half chip performance is better than full chip in both DC and NC code acquisition methods.